Strengthening of Edge and Corner Columns using Concrete Jackets - Eid Nasr, Mahmoud; Nour Fayed, Mohamed; El-Arabaty, Hisham Ahmed; Al-Azzouny, Mohamed (Civil Engineering Journal, 2021)
Strengthening of columns using concrete jackets depends on friction at the interface between them. So strengthening of edge and corner columns in only one story needs a large cross section area due to the shortage of friction length which leads to architectural issues. This research aims to study strengthening the edge and corner columns using a concrete Jacket in more than one story which increases the friction area between the Jacket and the original column. As a result, the load transferred from original column to the jacket will be increased. Thirteen models were done using ANSYS program to study the effect of various factors on the Jacket capacity such as the number of strengthened floors, the Jacket type (two sides or three sides), and whether there were shear connectors or not. The results showed that in the case of the edge and corner columns, it is preferable to strengthen the column by making a concrete Jacket on at least two or three floors to increase the surface area, which leads to increase the friction and thus increases the capacity of the strengthened column by an acceptable percentage. The results of ANSYS models were compared with the Indian code IS 15988 (2013) and the results were shown differently because the code equations depend on the presence of a full bond between the concrete column and the Jacket, which does not occur, but rather the load is transferred by friction between the Jacket and the original column.Â Doi: 10.28991/cej-2021-03091716 Full Text: PDF